Advanced methodologies and technologies in government and society - Khosrow-Pour, Mehdi, 1951- (Advances in public policy and administration (APPA) book series., 2019)
"This book provides research on emerging methodologies in effective governing including sections on public sector management and socio-economic development. While highlighting the challenges facing government officials and law enforcement such as crisis response and natural disaster management, it shows how technology use can make those areas of government more efficient and improve preventative measures"--